Outage Analysis of Sparse Vector Coding-Based Downlink Multicarrier NOMA for URLLC - Sabapathy, Sundaresan; Maruthu, Surendar; Kumar, Lakshmi Sutha; Jayakody, Dushantha Nalin K. (IEEE internet of things journal, 2023)
Ultrareliable and low-latency communication (uRLLC) is a promising use case in the fifth generation and beyond systems for critical and delay-sensitive applications with aid of short-packet transmission. Nevertheless, multicarrier nonorthogonal multiple access (MCNOMA) is a promising technique to achieve spectral efficiency and massive connectivity, however, intercarrier interference (ICI) stands out to be a major downside. Recently, sparse vector coding (SVC) is proposed to fulfill the tradeoff between reliability and latency, thereby achieving the benchmarks of uRLLC. In this article, SVC-based downlink MCNOMA (SVC-MCNOMA) system is considered and first it is shown that SVC-MCNOMA is free from ICI due to the sparse nature of the information. Further, compressed sensing (CS)-based recovery at the receiver end helps in reducing the latency as well as enhances reliability. Moreover, to study the system performance, this article derives the closed-form outage expressions of the SVC-MCNOMA system over the Rician fading channel, and through Monte Carlo simulation, the analytical results are validated. The analyses demonstrate that SVC-MCNOMA outperforms conventional MCNOMA (C-MCNOMA), thereby achieving spectral efficacy, ultrareliability with low latency, and eradicates the effect of ICI.